2016
DOI: 10.1038/srep33882
|View full text |Cite
|
Sign up to set email alerts
|

The effect of particle properties on the depth profile of buoyant plastics in the ocean

Abstract: Most studies on buoyant microplastics in the marine environment rely on sea surface sampling. Consequently, microplastic amounts can be underestimated, as turbulence leads to vertical mixing. Models that correct for vertical mixing are based on limited data. In this study we report measurements of the depth profile of buoyant microplastics in the North Atlantic subtropical gyre, from 0 to 5 m depth. Microplastics were separated into size classes (0.5–1.5 and 1.5–5.0 mm) and types (‘fragments’ and ‘lines’), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(147 citation statements)
references
References 38 publications
5
138
0
4
Order By: Relevance
“…It is unclear how plastics relate to the drifters. Depending on their rising velocity, and wind and wave conditions (Brunner et al, ; Kukulka & Brunner, ; Kukulka et al, ), plastics drift both on the sea surface and submerged in the upper ocean (Kooi et al, ; Reisser et al, ). As a result, both types of drifters are possible valid proxies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear how plastics relate to the drifters. Depending on their rising velocity, and wind and wave conditions (Brunner et al, ; Kukulka & Brunner, ; Kukulka et al, ), plastics drift both on the sea surface and submerged in the upper ocean (Kooi et al, ; Reisser et al, ). As a result, both types of drifters are possible valid proxies.…”
Section: Discussionmentioning
confidence: 99%
“…We also need to relate material properties of plastics to usuable transport properties, such as windage coefficient or rising velocity. Several studies have reported a correlation between the size of plastics and their rising velocity (Kooi et al, 2016;Lebreton et al, 2018;Reisser et al, 2015). Chubarenko et al (2016) determined the windage coefficient of plastics based on size and density, and Lebreton et al (2018) derived a windage coefficient for plastics in the North Pacific garbage patch by using it as a calibration parameter for their numerical model.…”
Section: Discussionmentioning
confidence: 99%
“…Infrequent surveys of the standing stock of litter on beaches provide crude estimates of debris types and abundance, but are biased by differential removal of litter items by beachcombing, clean-ups and beach dynamics. However, there is increased sampling of and analyses of micro-plastics on the ocean's surface (Reisser et al, 2013;Cózar et al, 2014;Eriksen et al, 2014;Isobe et al, 2015;Ryan, 2015;van Sebille et al, 2015) with fewer studies reporting on sub-surface micro-plastics (but see Reisser et al, 2015;Kooi et al, 2016).…”
Section: Current Assessmentmentioning
confidence: 99%
“…All data were corrected according to weather and sea conditions considering the possible "wind stress" effect, considering the wind speed (m/s) and wave height (m) applying the correction factors adopted by Kooi et al (2016) and Kukulka et al (2012).…”
Section: Counting and Characterization Of Microplastics And Mesoplasticsmentioning
confidence: 99%